Applications and Properties of Magnetic Nanoparticles - Paolo Arosio (Nanomaterials, 2021)
In the last few decades, magnetic nanoconstructs have attracted increasing attention due to, among others, their specific magnetic properties and huge number of applications in completely different fields [...]